To solve the quadratic equation \(-2x^2 + 3x - 1 = -2\), we first need to rearrange it into standard form \(ax^2 + bx + c = 0\).
Starting with the original equation:
\[ -2x^2 + 3x - 1 = -2 \]
Add 2 to both sides to get:
\[ -2x^2 + 3x - 1 + 2 = 0 \]
This simplifies to:
\[ -2x^2 + 3x + 1 = 0 \]
Now, we can use the quadratic formula to find the values of \(x\). The quadratic formula is:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \(a = -2\), \(b = 3\), and \(c = 1\).
Next, we calculate the discriminant (\(b^2 - 4ac\)):
\[ b^2 - 4ac = 3^2 - 4(-2)(1) = 9 + 8 = 17 \]
Now, we can substitute \(a\), \(b\), and the discriminant into the quadratic formula:
\[ x = \frac{-3 \pm \sqrt{17}}{2(-2)} \]
This simplifies to:
\[ x = \frac{-3 \pm \sqrt{17}}{-4} \]
Which can be written as:
\[ x = \frac{3 \mp \sqrt{17}}{4} \]
Now, we calculate the two potential solutions:
- For \(x_1 = \frac{3 + \sqrt{17}}{4}\)
- For \(x_2 = \frac{3 - \sqrt{17}}{4}\)
Calculating \( \sqrt{17} \):
\[ \sqrt{17} \approx 4.123 \]
Now substituting back into the equations:
- \(x_1 = \frac{3 + 4.123}{4} = \frac{7.123}{4} \approx 1.78075\)
- \(x_2 = \frac{3 - 4.123}{4} = \frac{-1.123}{4} \approx -0.28075\)
Rounding these solutions to the nearest hundredths:
- \(x_1 \approx 1.78\)
- \(x_2 \approx -0.28\)
So, the final rounded solutions are:
\[ x = -0.28 \quad \text{or} \quad 1.78 \]
Thus, the complete answer is:
\[ x = -0.28 \quad \text{or} \quad 1.78 \]